2023
DOI: 10.1007/s10661-023-11979-z
|View full text |Cite
|
Sign up to set email alerts
|

The technique of arsenic elimination from contaminated soil with enhanced conditions by electro-kinetic remediation

Laith Hamdan Hawal,
Ali Omran Al-Sulttani

Abstract: Remediation of arsenic-contaminated soil by the technique of electro-kinetic using various enhanced conditions is the thrust of this study. Many tests were performed with different operating conditions such as the electrodes solution (tap water) with a variable pH at (2, 5, and 8). Cyclodextrin (10% hydroxypropylbeta-cyclodextrin or HPCD) has been used as an activating agent that helps enhance this process of soil arsenic clean-up. Agricultural wastes (pomegranate peels) were used after treating them as an ads… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Electrokinetic remediation (EK) involves the migration of pollutants from the treatment area to the electrode area through ion exchange extraction. Hawal and Al-Sulttani [63] set up a chamber filled with contaminated soil. Tap water and cyclodextrin were used as an electrode solution and enhanced agent, respectively; it was demonstrated that EK could eliminate As from contaminated soil.…”
Section: Of 22mentioning
confidence: 99%
“…Electrokinetic remediation (EK) involves the migration of pollutants from the treatment area to the electrode area through ion exchange extraction. Hawal and Al-Sulttani [63] set up a chamber filled with contaminated soil. Tap water and cyclodextrin were used as an electrode solution and enhanced agent, respectively; it was demonstrated that EK could eliminate As from contaminated soil.…”
Section: Of 22mentioning
confidence: 99%